Synthesis of a Slow-Release Fertilizer Composite Based on Microcrystalline Cellulose from Coconut Husk Waste - Vicka Andini; Yoravika Dwiwibangga; Safniyeti Safniyeti; Nasywa Az Zahra; Ulfah Anis; Mega Elfia (Jurnal Kimia Sains dan Aplikasi, 2026)
This study reports the synthesis and evaluation of a biodegradable slow-release fertilizer based on microcrystalline cellulose (MCC) extracted from coconut husk waste from Seluma Regency, Bengkulu Province. MCC was prepared through sequential acid washing, alkaline delignification, bleaching, and acid hydrolysis. A composite fertilizer was synthesized by incorporating maleate-containing polymer segments into MCC through limited radical grafting and/or esterification, followed by incorporation of polydihydroxymethylurea potassium phosphate (PDMU–KP) using citric acid as an interaction agent. Fourier transform infrared (FTIR) analysis indicates the presence of carbonyl, amide, and phosphate-related functional groups associated with the composite structure. Scanning electron microscopy (SEM) revealed a dense and agglomerated composite morphology with a rough, layered surface and crystalline aggregates, while energy-dispersive X-ray (EDX) analysis verified the presence of C, N, O, P, and K elements within the copolymer matrix. X-ray diffraction (XRD) analysis showed a reduction in cellulose crystallinity after copolymerization, indicating the formation of a polymer composite. Nutrient release tests conducted in distilled water for 28 days demonstrated controlled and differential release behavior governed by polymer swelling and matrix relaxation processes. Phosphate exhibited a maximum release concentration of 0.398 mg/L on day 7, followed by a gradual decrease to 0.058 mg/L by day 28. In contrast, nitrogen release occurred more gradually, reaching a maximum concentration of approximately 3.08 mg/L on day 14 before declining at later stages. These results indicate that the MCC-g-PMA/PDMU–KP copolymer provides sustained nutrient release with distinct release maxima for phosphorus and nitrogen, highlighting its potential as a cellulose-based slow-release fertilizer designed to improve nutrient use efficiency and reduce nutrient losses, derived from locally available coconut husk waste.